PENGARUH LEADER MEMBER EXCHANGE,DAN KEAHLIAN TEKNOLOGI INFORMASI TERHADAP KINERJA GURU SMP DI KABUPATEN PURWAKARTA - Patoni Patoni (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This research manifests the effect of Leader Member Exchange, and Information Technology Expertise on the Performance of Middle School Teachers in Purwakarta Regency. The purpose of this study was to determine the effect of leader member exchange, and information technology expertise on the performance of junior high school teachers in Purwakarta with the research method used was descriptive analytical. The research data were obtained from questionnaires which were distributed directly to 95 teachers of state junior high schools in Purwakarta Regency, which were spread across 51 junior high schools through Google Form. Data processing was performed using the SPSS program version 24.0 which included a validity test, a reliability test, a correlation test, a multiple linear regression test, and a classic assumption test. The results showed that partially leader member exchange had a significant effect on the performance of junior high school teachers in Purwakarta by 54.40%, and information technology expertise significantly influenced the performance of junior high school teachers in Purwakarta by 49.30%. Simultaneously showed a significant influence of leader member exchange and information technology expertise on the performance of junior high school teachers in Purwakarta Regency by 64.21% and the remaining 35.79% was influenced by other factors not examined by researchers.